Correlation incidence between infectious bursal disease and aflatoxicosis in broilers chicken farms in Nineveh province, Iraq - Zaid Th. Al-Taee; Mohammed Gh. Saeed (Iraqi Journal of Veterinary Sciences, 2023)
This study aimed to investigate the incidence of infectious bursal disease IBD and aflatoxicosis with the correlation between them in broilers of six different areas in Nineveh Province, Iraq, which include: Mosul, Talafer, Hamdanya, Bartella, Baaj, and Gayara for six months (October 2021-March 2022). The necropsy of the suspected infected birds and blood sampling were conducted on 25 birds for each area to diagnose IBD. Samples of broiler feed were collected from the same farms to diagnose aflatoxin B1. The detection of both IBD and aflatoxicosis occurred by the ELISA technique. The necropsy results showed hydropericardium, paleness or congestion, friable and swelling of the liver, kidneys, and bursa of Fabricius, with more severe lesions in a few sporadic cases as gelatinous fluid surrounding the heart, intense paleness of the liver, kidney, and enlarged bursa of Fabricius. The detection of IBD revealed that the positive results were 142, and the negative results are 8 birds out of a total of 150 suspected broiler attributed to the subclinical infection according to the vaccine index equation. Also, positive aflatoxin B1 concentrations were recorded in all broiler feed in the 6 areas as the highest concentration mean was 0.23 ppb and the lowest concentration mean was 0.186 ppb in Mosul and Baaj, respectively. This study indicated a positive correlation between IBD and aflatoxin B1 but was not statistically significant.